Phylogenetic analysis, mixed infection and seed transmission of Pea seed-borne mosaic virus in Ethiopia - Ademe, Anteneh; Kumari, Safaa; Moukahel, Abdulrahman; Alemu, Tesfaye; Abraham, Adane; Aynewa, Yetsedaw; Guadie, Demsachew; Kemal, Seid Ahmed (Elsevier, 2025)
Pea seed-borne mosaic virus (PSbMV) is a significant pathogen affecting the yield and quality of lentil and chickpea crops in Ethiopia's major legume-producing regions, Amhara and Oromia. This study focuses on characterizing PSbMV and its seed transmission rates, including mixed infections under field conditions. Tissue blot immunoassay (TBIA) analysis revealed that 56.2 % of tested lentil and chickpea samples were infected with PSbMV, often in mixed infections. PSbMV seed transmission rates varied widely among tested lentil genotypes, with the widely grown improved lentil cultivar Alemaya (FLIP 89-63 L) showing a transmission rate as high as 13.5 %. To characterize the isolates, the partial polyprotein gene was amplified and sequenced. Analysis of these sequences showed nucleotide identities ranging from 90.5 % to 100 %. Phylogenetic analysis classified Ethiopian PSbMV isolates (from lentil and chickpea) into four major clades and four subclades. Five lentil isolates (EthLe204-18, EthLe547-18, EthLe12-19, EthLe84-19, and EthLe214-33-19) and one chickpea isolate (EthCp115-19) clustered in subgroup BI, while isolate EthLe343-18 clustered into subgroup BII with an American pathotype-2 isolate (AJ252242). Isolates EthLe7-21 and EthLe381-21 clustered with an Australian P-2 isolate (HQ185579) into group D. Further analysis using RDP indicates intraspecific recombination only in isolate EthLe214-19, with fragments derived from EthLe343-18 and EthLe204-18 as major and minor parents, respectively. No recombination events were detected in the other isolates. This study suggests that variations in lentil genotype resistance to seed infection could be leveraged for resistance breeding, and the impacts of mixed infections on lentil crops warrant further investigation.